A grammar of Upper Tanana. - Lovick, Olga Charlotte (University of Nebraska Press, 2019)
A Grammar of Upper Tanana is a comprehensive text that performs the impressive task of providing a linguistically accurate written record of the endangered Upper Tanana language.